Interleukin-6 in schizophrenia is associated with negative symptoms, side effects of therapy and smoking: results of a pilot study - T. V. Zhilyaeva; A. S. Piatoikina; G. V. Rukavishnikov; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Interleukin-6 (IL-6) is one of the most important pro-inflammatory markers with immunomodulatory activity associated with schizophrenia. The possible involvement of interleukin-6 in the etiopathogenesis of schizophrenia and the development of different clusters of symptoms remains debatable; the relationship between an increase in interleukin-6 and a number of possible confounding factors, including smoking, has not yet been studied. The aim of this work was the pilot evaluation of the serum IL-6 level in patients with schizophrenia compared with healthy controls, as well as its association with clinical symptoms, socio-demographic factors and smoking. Materials and methods: 43 patients with schizophrenia and 24 healthy volunteers were examined. The determination of IL-6 was carried out by enzyme immunoassay. All patients were assessed using the Positive and Negative Schizophrenia Syndrome Scale (PANSS), The UKUSERS-Clin Therapeutic Side Effects Scale (UKU), Simpson-Angus Scale (SAS), the Abnormal Involuntary Movements Scale (AIMS), Barnes Akathisia Scale (BARS), Personal and Social Functioning Scale (PSP). Results: In patients with schizophrenia in a Russian sample, serum IL-6 levels were significantly associated with smoking status (p = 0.0017), the severity of negative symptoms and symptoms of the PANSS general psychopathology scale (p=0.014 and p=0.038, respectively), disorders of personal and social functioning (PSP, p=0.011), as well as side effects measured using the UKU scale (general, p=0.038, 0041 and extrapyramidal, p=0.018), as well as drug-induced parkinsonism (p=0.043), dyskinesia (p=0.0084) and akathisia (p=0.043). All scores are worse in patients with nicotine addiction. The occurrence of extrapyramidal symptoms (EPS) in response to standard doses of antipsychotics (AP) can serve as a clinical marker of possible immune-inflammatory disturbances in patients with schizophrenia, and the smoking status can act as a provocing factor for increasing of latent inflammation. Replication of the study is required to confirm the findings.